Hepatitis B and renal failure: prevalence and associated factors in National University Hospital Center of Cotonou - SEHONOU, JEAN; KPOSSOU, ABOUDOU RAÏMY; AMANDA, Taofick Oyétoundé; SOKPON, Comlan N’déhougbèa Martin; VIGNON, KOFFI RODOLPH; VIGAN, JACQUES (My University, 2018)
Introduction: the association between the kidneys and hepatitis B is complex. This study aims to determine the prevalence and factors associated with renal disease in people living with hepatitis B virus (PLHBV) in Cotonou. Methods: we conducted a cross-sectional, descriptive and analytical study in the Hepatogastroenterology Department at the National University Hospital Center in Cotonou over the period May -August 2017. All the patients with positive hepatitis B surface antigen (HBS Ag) test hospitalized in the study period were included. The diagnosis of renal failure was retained in patients with glomerular filtration rate less than 90 mL/min/1.73 m2 (estimated with MDRD Equation). Results: the study involved 105 patients with positive hepatitis B surface antigen (HBS Ag) test Among them, 65 (61.9%) were under anti-HBV treatment ( 62 of them were under tenofovir ); 41 patients had renal failure (39%) with tubular involvement (2 cases) and glomerular involvement (4 cases). Renal function had got progressively worse over time in 22 patients (21%) and had improved in 6 patients (5.7%). Univariate analysis showed that factors associated with the occurrence of renal failure were: age greater than 50 years (p = 0.0125), high blood pressure (p = 0.0037), initially abnormal renal function (p < 0.0003) and co-medications (p = 0.0007). Anti-HBV treatment wasn't associated with the occurrence of renal failure (p = 0.2887). Conclusion: the prevalence of renal failure in PLHBV was high (39%). Age, arterial hypertension, pre-existing renal failure and co-medications were identified as factors associated with decline in renal function in PLHBV.
Keywords: Renal failure; hepatitis B; associated factors